2014
DOI: 10.1007/s10815-014-0193-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone (AMH): a reliable biomarker of oocyte quality in IVF

Abstract: Patients with AMH < 0.47 ng/ml should be advised before starting a stimulated IVF cycle of the poorer prognosis compared to our reference population independently of their age, total exogenous FSH dosage and number of eggs retrieved. Therefore, AMH could enable a more individualized number of embryo transfer policy based on oocyte quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 34 publications
2
30
0
3
Order By: Relevance
“…To confirm that AMH is a better marker of COH response and IVF outcomes, we compared it with AFC. Our results confirm previously reported findings [24,25,26] that attested that AFC is less effective than AMH in predicting IFV outcomes; AFC was only associated with number of frozen embryos. La Marca et al [27] indicated that AMH has primarily been related to assisted reproduction because of its strong association with oocyte yield after COH.…”
Section: Discussionsupporting
confidence: 92%
“…To confirm that AMH is a better marker of COH response and IVF outcomes, we compared it with AFC. Our results confirm previously reported findings [24,25,26] that attested that AFC is less effective than AMH in predicting IFV outcomes; AFC was only associated with number of frozen embryos. La Marca et al [27] indicated that AMH has primarily been related to assisted reproduction because of its strong association with oocyte yield after COH.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the specific population of breast cancer patients and their goal of fertility preservation in that study, embryo cryopreservation was a freeze-all condition performed at the pronuclear stage. Several studies have examined whether AMH levels are associated with successful supernumerary embryo cryopreservation, with some data showing a statistically significant correlation (16)(17)(18) and other data showing no difference (25). The cryopreservation of supernumerary embryos in the aforementioned studies was performed on day 3.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of embryo cryopreservation, AMH has been shown to predict the availability of pronuclear embryos for cryopreservation in breast cancer patients (15). In addition, several studies have found that the AMH level may predict the availability of good-quality supernumerary day-3 embryos for cryopreservation (16)(17)(18). We sought to determine whether the AMH level can predict the availability of good-quality supernumerary blastocysts for cryopreservation.…”
mentioning
confidence: 99%
“…For example, during ovarian stimulation for IVF, an increase in soluble Fas (sFas) binding to Fas ligand (FasL) in follicular fluid prevents FasL interaction with its cell-surface receptor as a trigger for apoptosis, thereby inhibiting Fas-mediated apoptosis of mural granulosa and cumulus cells (132). In addition, AMH, a TGFbrelated peptide used to predict oocyte yield, but not necessarily oocyte quality (133)(134)(135)(136)(137), diminishes in the growing follicle (138), where it also predicts follicle responsiveness to FSH in normoandrogenic ovulatory women undergoing IVF (139).…”
Section: Proteins and Proteomicsmentioning
confidence: 99%